Women Witnesses to the Risen Lord - Simmonds, Andrew (Verbum Vitae, 2022)
Under Jewish law, the witnessing of Jesus as resurrected must occur by the third-day after death. Later witnessing can be corroborative, but the third-day witnessing is crucial. In Matthew and John, the sole percipient witnesses on the third-day are women, plural in Matthew, a single woman in John. This seems to cast doubt on Jesus’ resurrection because in Greek, Roman, and Jewish culture, women were ineligible as witnesses or were considered vastly inferior as witnesses to men. Celsus inveighed, “Who saw this? A hysterical female!” Communicating to outsiders, having women witness casts aspersions on Jesus’ resurrection making Christianity appear unthreatening to the imperial order. However, for Jews aware of the celebrated exception in the Pharisaic/rabbinic oral law/tradition that accepted women’s testimony in the circumstances found in the gospels, having specifically women witness makes their testimony more credible than had the witnesses been men or any combination of men and women. Women witnessing the risen Lord fits within the interstices of the Law, so that, not just human testimony, but the Law lends its imprimatur endorsing Jesus.